Review of the First Quarter of 1933 - Crum, W. L.; Hubbard, J. B. (The Review of Economics and Statistics, 1933)
GENERAL business in the United States, as reflected by the B curve of the index chart (page 63), was at about the same average level in the first quarter of this year as in the preceding quarter a condition which had not prevailed since the second quarter of I930. The course of general business during the quarter was downward; and the March figure was undoubtedly at a new low level, somewhat below that of November I932. Exact measurement, either for March or the quarter as a whole, is impossible because of the temporary omission of bank debits figures due to the March bank moratorium. (See technical explanation below, page 73.) The declines in February and March were not exceptionally severe, particularly when allowance is made for the apparent sharpness of the revival late in March. The outstanding developments of the first quarter of I933 were in banking and credit. Various disquieting influences, largely political and psychological, led to renewed and intensified runs upon banks. Local moratoria became necessary, and presently a general suspension of gold payments and a temporary closing of all banks could not be avoided. March was largely devoted to the adoption of emergency measures which permitted the reopening of most banks; and certain other steps taken tended to restore confidence. The quarter closed with faith and hope rapidly reviving; and the imminence of inflation, which was to develop early in April, had not yet become a decisive factor in the reckoning of most business and financial leaders. Speculation, as reflected by Curve A (page 63), declined during the quarter; but the net movement for March as a whole was nearly horizontal. The most striking manifestations of the banking and monetary crisis were thus not in speculation but in the field of money and credit money rates and the currency and banking data.